Pengaruh Kualitas Pelayanan Kapal Reguler Terhadap Kepuasan Pelanggan Pada Pelabuhan Bakauheni - Fitriani, Riska; Fashandika Eka Putra, Erlandra; Nailah, Haura; Ma’ruf; Permana, Rafael (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2024)
This study aims to analyze the effect of regular ship services on customer satisfaction at Bakauheni Port. Using a quantitative descriptive approach, data was collected through observations, interviews, and also literature study surveys and distributing questionnaires to regular ship passengers in the first quarter of 2024. The population for this study is passengers who use regular ship services at Bakauheni Port. The research was conducted by using a questionnaire and distributed to 97 respondents using random sampling. The research method applied is quantitative analysis with multiple regression. The findings of the study indicate that there are dimensions of quality in service that have a significant influence on customer satisfaction. The validity, reliability, and normality tests resulted in normal data distribution. Multiple linear regression analysis results in Y = 0.876 + 0.169X1 + 0.010X2 + 0.365X3 + 0.210X4 + 0.157X5 + e. From the analysis results it can be seen that the Responsiveness variable (X3) of 0.365 has the greatest influence on customer satisfaction, followed by the Assurance variable (X4) of 0.210, the Tangibles variable (X1) of 0.169, the Empathy variable (X5) of 0.157, and the Reliability variable (X2) of 0.010. In the calculation of hypothesis testing, the variables that have a positive effect are the Responsiveness variable with a sig result of 0.001, and Assurance with a sig result of 0.037.